Critical medical ecology and SARS-COV-2 in the urban environment: a pragmatic, dynamic approach to explaining and planning for research and practice - Timothy De Ver Dye; Erin Muir; Lorne Farovitch; Shazia Siddiqi; Saloni Sharma (BMC, 2020)
Abstract Background Practitioners and researchers in the midst of overwhelming coronavirus disease 2019 (COVID-19) outbreaks are calling for new ways of looking at such pandemics, with an emphasis on human behavior and holistic considerations. Viral outbreaks are characterized by socio-behaviorally-oriented public health efforts aimed at reducing exposure and prevention of morbidity/mortality once infected. These efforts involve different points-of-view, generally, than do those aimed to understand the virus' natural history. Rampant spread of SARS-CoV-2 infection in cities clearly signals that urban areas contain conditions favorable for rapid transmission of the virus. Main text The Critical Medical Ecology model is a multidimensional, multilevel way of viewing pandemics comprehensively, rooted simultaneously in microbiology and in anthropology, with shared priority for evolution, context, stressors, homeostasis, adaptation, and power relationships. Viewing COVID-19 with a Critical Medical Ecological lens suggests three important interpretations: 1) COVID-19 is equally - if not more - a socially-driven disease as much as a biomedical disease, 2) the present interventions available for primary prevention of transmission are social and behavioral interventions, and 3) wide variation in COVID-19 hospitalization/death rates is not expected to significantly be attributable to a more virulent and rapidly-evolving virus, but rather to differences in social and behavioral factors - and power dynamics - rather than (solely) biological and clinical factors. Cities especially are challenged due to logistics and volume of patients, and lack of access to sustaining products and services for many residents living in isolation. Conclusions In the end, SARS-CoV-2 is acting upon dynamic social human beings, entangled within structures and relationships that include but extend far beyond their cells, and in fact beyond their own individual behavior. As a comprehensive way of thinking, the Critical Medical Ecology model helps identify these elements and dynamics in the context of ecological processes that create, shape, and sustain people in their multidimensional, intersecting environments.